Relationship between 25(OH)D levels and athletic performance in elite Polish judoists - Książek, Anna; Dziubek, Wioletta; Pietraszewska, Jadwiga; Słowińska-Lisowska, Małgorzata (Biology of Sport, 2018)
There is a growing body of evidence for a role of vitamin D in muscle function and for its influence on athletic performance, injury profile and recovery in well-trained athletes. The aim of our study was to assess the relationship between 25(OH)D levels and hand grip strength, lower limb isokinetic strength and muscle power in elite judoists. We enrolled 25 Polish elite judoists. The mean age was 21.9±9.8 years, the mean height was 179.2±6.6 cm, the mean body mass was 79.1±8.7 kg, and the mean career duration was 11.5±3.9 years. Serum levels of 25(OH)D and parathormone (PTH) were measured by electrochemiluminescence (ECLIA) using the Elecsys system (Roche, Switzerland). Serum calcium was determined by colorimetry using the Konelab 60 system from bioMérieux (France). Lower limb strength was tested with the Biodex Multi-Joint 4 Isokinetic Dynamometer (Biodex Medical System, New York, USA), and hand grip strength was measured with a manual dynamometer (TAKEI, Japan). Muscle power was determined with the electronic jump mat OptoJump (Microgate, Bolzano, Italy). Our study showed decreased serum 25(OH)D levels in 80% of the professional judoists. The results also demonstrated a statistically significant positive correlation between vitamin D levels and left hand grip strength, muscle power assessed by vertical jump, and total work in left and right knee extensors at an angular velocity of 60°/s. Based on our results it can be concluded that in well-trained professional athletes, there may be a relationship between serum levels of 25(OH)D and skeletal muscle strength, power, and work.